2020
DOI: 10.3892/etm.2020.9312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of unilateral intravitreal bevacizumab injection on the incidence of symptomatic choroidal neovascularization in the fellow eye in patients with neovascular age‑related macular degeneration (Review)

Abstract: Neovascular age-related macular degeneration (neovascular ARMD) represents only 10% of ARMD cases but is responsible, if untreated, for quick and severe central vision loss due to major macular changes. The presence of choroidal neovascularization (CNV) in one eye is associated with an approximately 10% risk of CNV development in the fellow eye each year. Intravitreal anti-VEGF therapy has quickly evolved as the standard treatment in neovascular ARMD in the last decade due to significant anatomical and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Maria Andrea Gamulescu et al did not state a signi cant change in the central retinal thickness of the fellow eye after intravitreal ranibizumab injection to the rst eye in bilateral wet AMD patients and concluded that systemic cross-over of ranibizumab was not enough to reach therapeutic levels in the fellow eye [22]. On the other hand, Daniel et al observed a reduced incidence of symptomatic CNVM in the fellow untreated eye after intravitreal bevacizumab injection in unilateral wet AMD cases [23]. Another study demonstrated that fellow eyes of unilateral wet AMD patients that later converted to wet AMD presented with a better vision and required less injections in the disease course compared to the primary eyes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Maria Andrea Gamulescu et al did not state a signi cant change in the central retinal thickness of the fellow eye after intravitreal ranibizumab injection to the rst eye in bilateral wet AMD patients and concluded that systemic cross-over of ranibizumab was not enough to reach therapeutic levels in the fellow eye [22]. On the other hand, Daniel et al observed a reduced incidence of symptomatic CNVM in the fellow untreated eye after intravitreal bevacizumab injection in unilateral wet AMD cases [23]. Another study demonstrated that fellow eyes of unilateral wet AMD patients that later converted to wet AMD presented with a better vision and required less injections in the disease course compared to the primary eyes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Anakinra, a recombinant IL-1 receptor antagonist [ 169 ], may control the inflammatory activation mediated by IL-1, with reduction or discontinuation of steroids in patients at risk of death or serious morbidity [ 158 ]. Bevacizumab is a humanized monoclonal antibody against VEGF (reviewed in [ 170 ]) used in patients with IRIS who had a marked improvement in both the functional and anatomical outcomes without any deterioration at 12 months follow-up [ 160 ]. Additionally, the therapeutic effect of Adalimumab, an anti-TNF monoclonal antibody, was tested in a TB-IRIS case of [ 161 ], showing efficacy in IRIS management without compromising control of mycobacterial or HIV infection.…”
Section: Host-directed Therapies To Prevent and Treat Iris In Plwhmentioning
confidence: 99%
“…IOP may be difficult to measure, because of an altered corneal status, as is also the case in anterior segment pathology or after corneal surgery [11][12][13][14]. Moreover, decreased visual acuity with associated impaired fixation may preclude IOP measurement, similarly to ocular media opacities and advanced macular disease [15][16][17]. What is more, a correct evaluation of the optic nerve is not always possible due to poor fixation and difficult visualization of the retina.…”
Section: Introductionmentioning
confidence: 99%